Genome stabilization by RAD51‐stimulatory compound 1 enhances efficiency of somatic cell nuclear transfer‐mediated reprogramming and full‐term development of cloned mouse embryos. (21st May 2021) - Lee, Ah Reum; Park, Ji‐Hoon; Shim, Sung Han; Hong, Kwonho; La, Hyeonwoo; Park, Kyung‐Soon; Lee, Dong Ryul
Abstract: Objectives: The genetic instability and DNA damage arise during transcription factor‐mediated reprogramming of somatic cells, and its efficiency may be reduced due to abnormal chromatin remodelling. The efficiency in somatic cell nuclear transfer (SCNT)‐mediated reprogramming is also very low, and it is caused by development arrest of most reconstituted embryos. Materials and Methods: Whether the repair of genetic instability or double‐strand breaks (DSBs) during SCNT reprogramming may play an important role in embryonic development, we observed and analysed the effect of Rad 51, a key modulator of DNA damage response (DDR) in SCNT‐derived embryos. Results: Here, we observed that the activity of Rad 51 is lower in SCNT eggs than in conventional IVF and found a significantly lower level of DSBs in SCNT embryos during reprogramming. To address this difference, supplementation with RS‐1, an activator of Rad51, during the activation of SCNT embryos can increase RAD51 expression and DSB foci and thereby increased the efficiency of SCNT reprogramming. Through subsequent single‐cell RNA‐seq analysis, we observed the reactivation of a large number of genes that were not expressed in SCNT‐2‐cell embryos by the upregulation of DDR, which may be related to overcoming the developmental block. Additionally, there may be an independent pathway involving histone demethylase that can reduce reprograming‐resistance regions. Conclusions: This technology can contribute to the production of comparable cell sources for regenerative medicine. Abstract : We determined the effect of upregulation of Rad51 homologous 1 (RAD51) by treatment with RAD51‐stimulatory compound 1 (RS‐1) on the role of DSB repair during somatic cell nuclear transfer (SCNT) reprogramming and the improvement of embryonic development by reducing DNA damage. Therefore, supplementation with RS‐1 during reprogramming can recover RAD51 activity and improve the derivation efficiency of PSCs, and would be an efficient, safe and simple protocol for improving the efficacy of SCNT technology.